Perkembangan Kecerdasan Spriritual Anak melalui Dukungan Orang Tua di TK Teladan Fatimah Azzahra - Diah Nurkholishoh; Yulianah Suvina; Ananti Tri Harani; Faizatul Fitriyah (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2024)
Spiritual intelligence is the main foundation in forming children's character and morals. One important component in developing this intelligence is through example from parents who are the closest figures to children. This research was conducted to find out more deeply about parental support in the process of developing children's spiritual intelligence. The method used is qualitative with a case study design. Data collection was carried out through interviews with parents and observations of children's development. The conclusion of this research emphasizes that to form good character in children, support from a positive environment is needed and parents have an important role in the spiritual development of early childhood, especially in the Fatimah Azzahra Kindergarten.